Vliv komplexity prostředí a rizika predace na utváření společenstev v malých stojatých vodách - Soukup, Pavel (Jihočeská univerzita, 2015)
The effects of habitat complexity and predation risk on community assembly in small standing waters are reviewed. Both lethal and nonlethal predator effects are discussed. Emphasis is put on the role of omnivorous predators which do not fit into the standard food chain model. The review is complemented by a manuscript intended for publication in Freshwater Biology. It reports the results of a mesocosm experiment focusing on the effects of both lethal and nonlethal predation risk, induced by the invasive crayfish species Orconectes limosus, and habitat complexity on the abundance and biomass of macroinvertebrates in a naturally assembled community.
Habitat complexity and predation risk effects on community assembly in small standing waters
Keywords: community assembly; predation risk; habitat complexity; Eastern crayfish; size structure; community assembly; predation risk; habitat complexity; Eastern crayfish; size structure